Integrasi teknologi dalam pendidikan anak usia dini: menilai dampaknya pada perkembangan kognitif - Salim, Nur Agus (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2022)
This research aims to evaluate the impact of technology integration in early childhood education on their cognitive development. Using a literature review, this research observes the use of technology in the classroom and analyzes data from research results and literature. The results show that technology, when used in a balanced and age-appropriate manner, supports improved cognitive skills such as language and problem solving. However, misuse or overuse can negatively impact a child's social and emotional skills. The study's conclusions emphasize the importance of structured and supervised use of technology in early childhood education, suggesting a balance between technology use and traditional learning activities to support holistic and healthy cognitive development.